ОФОРМЛЕНИЕ РОДА АНГЛИЦИЗМОВ И РОМАНИЗМОВ В НЕМЕЦКОМ ЯЗЫКЕ - Хамидов, Н.Ш.; Палуанова, М.; Бабаева, Г. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of foreign language nouns involved in a German-speaking environment, and formed by the category of gender (also, the categories of case and number). In the article the author revealed their interrelations in many languages.